More Than Spikes: On the Added Value of Non-linear Intracranial EEG Analysis for Surgery Planning in Temporal Lobe Epilepsy - Müller, Michael; Dekkers, Martijn; Wiest, Roland; Schindler, Kaspar; Rummel, Christian (Frontiers in Neurology, 2022)
Epilepsy surgery can be a very effective therapy in medication refractory patients. During patient evaluation intracranial EEG is analyzed by clinical experts to identify the brain tissue generating epileptiform events. Quantitative EEG analysis increasingly complements this approach in research settings, but not yet in clinical routine. We investigate the correspondence between epileptiform events and a specific quantitative EEG marker. We analyzed 99 preictal epochs of multichannel intracranial EEG of 40 patients with mixed etiologies. Time and channel of occurrence of epileptiform events (spikes, slow waves, sharp waves, fast oscillations) were annotated by a human expert and nonlinear excess interrelations were calculated as a quantitative EEG marker. We assessed whether the visually identified preictal events predicted channels that belonged to the seizure onset zone, that were later resected or that showed strong nonlinear interrelations. We also investigated whether the seizure onset zone or the resection were predicted by channels with strong nonlinear interrelations. Epileptic spikes and the seizure onset zone predicted the resected brain tissue much better in patients with favorable seizure control after surgery than in unfavorable outcomes. Beyond that, our analysis did not reveal any significant associations with epileptiform EEG events. Specifically, none of the epileptiform event types did predict nonlinear interrelations. In contrast, channels with strong nonlinear excess EEG interrelations predicted the resected channels better in patients with favorable outcome. Our study indicates that nonlinear excess EEG interrelations are not strictly associated with epileptiform events, which are one key concept of current clinical EEG assessment. Rather, they may reveal relevant additional information. We make the EEG epochs and expert annotations publicly available to foster similar analyses for other quantitative EEG methods.